50 years of Malaysian agriculture: transformational issues challenges & direction - Fatimah, Mohd Arshad; Raja Abdullah, Nik Mustapha; Kaur, Bisant; Abdullah, Amin Mahir (Universiti Putra Malaysia Press, 2007)
The Malaysian agricultural sector has come a long way since Malaysia achieved its independence fifty years ago. The sector which kicked off as the major earner for the country’s coffer in the 1950’s has been reduced to one of many sectors in the country’s economic statistics. At the turn of the 21st century, agriculture accounted for less than one-tenth of the country’s Gross Domestic Product and export earnings. The industrial sectors such as services, electrical and electronics and construction, have become the country’s engines of growth.This trend is applauded by development economist as a testament to the role of the agriculture sectors as the catalyst to industrialization in the early stage of development. Before the financial crisis in 1997, Malaysia was destined to be one of the newly industrialized economies in the Asian region with potentials to be a developed economy. The pace of rapid growth suffered a temporary setback after the crisis, but the country was able to recover and continue with developmental programmes towards a fully developed nation by the second decade of the century. The history of Malaysian agriculture was charted by the colonial masters since the nineteenth century which was responsible in shaping the Industry in the years that followed.